AN ANALYSIS OF NARRATIVE TEXT WRITING MADE BY THE TENTH GRADERS OF ACCELERATION CLASS AT SMA NEGERI 1 SIDOARJO (RETAIN, 2014)
AN ANALYSIS OF NARRATIVE TEXT WRITING MADE BY THE TENTH GRADERS OF ACCELERATION CLASS AT SMA NEGERI 1 SIDOARJO Putri Ulul Apriliyani English Departement, Languages and Arts Faculty, State University of Surabaya putritik@gmail.com Himmawan Adi Nugroho, S.Pd., M.Pd English Departement, Languages and Arts Faculty, State University of Surabaya himmawan_95@yahoo.co.id Abstrak Pemerintah menetapkan Bahasa Inggris sebagai salah satu mata pelajaran yang harus diterapkan disetiap level pendidikan. Hal ini dikarenakan Bahasa Inggris dipakai sebagai foreign language oleh negara kita. Untuk menguasai Bahsa Inggris sebagai foreign language ini, para siswa diharapkan menguasai keempat komponen dasar yang dimiliki oleh Bahasa Inggris. Salah satu kemampuan dasar tersebut adalah menulis. Menulis bisa membuat siswa menuangkan ide-ide yang mereka miliki agar dapat diketahui oleh orang lain dalam bentuk tulisan (Hyland,2002). Untuk membantu para guru untuk mengajar pelajaran menulis dalam Bahasa Inggris dapat digunakan jenis teks sebagai alat penunjang. Salah satu jenis teks yang dominan diajarkan di SMA adalah Narrative. Jadi, para siswa dituntut untuk bisa menguasai teks ini secara lisan dan tulisan. Secara tulisan, para siswa dituntut untuk dapat menulis teks narrative mereka sendiri berdasarkan generic structure dan language features dari teks tersebut. Berkaitan dengan hal itu, sebuah penelitian kualitatif deskriptif digunakan untuk menganalisis teks narrative yang telah ditulis oleh siswa. Siswa kelas X-Akselerasi dibagi menjadi tiga grup yang berbeda berdsarkan kemampuan mereka dalam menguasai pelajaran Bahasa Inggris. Instrumen penelitian yang dipakai dalam penelitian ini ada tiga jenis yaitu; checklist, rubrik penilaian dan juga peneliti. Selain itu, semua teks narrative yang ditulis oleh siswa dikumpulkan untuk dinilai dan dianalisis oleh peneliti. Hasil analisis menunjukkan bahwa semua siswa dapat menuliskan teks narrative mereka sendiri berdsarkan generic structure dan language features teks tersebut. Tapi, ada beberapa siswa yang masih membuat kesalahan pada saat menuliskan generic structure dan language features dari teks mereka. Kesalahan yang paling banyak mereke buat adalah menggunakan past tense sebagai dominan tense didalam narrative text. Pada akhirnya, para guru disarankan untuk memberi penjelasan yang jelas kepada para siswa tentang tata cara menulis teks narrative yang baik dan benar. Selain itu, para guru sebaiknya juga harus menjelaskan penggunaan past tense sebagai tenses yang dominan dipakai didalam teks narrative sebelum mereka memberi tugas kepada siswa untuk menuliskan teks narrative mereka sendiri. Karena sebagian besar kesalahan siswa terletak pada penggunaan past tense ini. Kata Kunci: narrative text, generic structure, language features Abstract Since English is used as foreign language in our country, it becomes important subject in every education level. Four basics skills is needed to help the students learning English as their foreign language. One of the important skill is writing. Writing can make the students take out their mind and put it in the other form that people can read and consider (Hyland, 2002). Therefore, text type is appropiate tools for the teachers to teach writing for the students. Narrative is one of the text type that mostly taught in High School. It makes the students have to master this text both in written and spoken form. In written form, the students must be able to compose their narrative text correctly based on its generic structure and language features. To deal with, a descriptive qualitative design is used to analyze the students’ narrative composition that they wrote as their writing assignment. The students in X-Acceleration class divided into three groups based on their ability in mastering English and nine students are taken as representatives. This study uses checklist, assessment scoring rubric, and the researcher as the research instruments. Moreover, all of the students’ original narrative compositions are collected to be analized and scored. The result shows that all of the samples are able to write their narrative composition completely in the term of generic structure and language features. But, some students still made some errors when applied generic structure and language features of narrative text. The errors that mostly appeared in the students’ narrative composition is the use of past tense as dominant tense in this text. At the end, it suggests that the teacher should give a clear explanation and example for the students about how to compose a good narrative text is. Moreover, since most of the students made error when applied past tense in their writing, it is better for the teachers to give brief and clear explanation about it before they ask the students to write narrative text theirselves. Keywords: narrative text, generic structure, language features INTRODUCTION Language is one most important thing which can support our communication in our life. It is supported by (Oxford Learner's Pocket Dictionary, 2008) that language is a system of sounds, words used by humans to communicate thoughts and feelings. This definition means that every people can use language to express everything that they feel, such; their thought, emotion, ideas, and etc. Expressing all of those feelings, people can use language in two ways, spoken and written. Moreover, both of this way can be very useful device for humans to communicate with others. Nowdays, English becomes an International language which is used by all of the country as their second language or their foreign language. Since our country uses English as ours Foreign language, the goverment has decided to include English as one of important subject in every education level. It purposes that all of students in our country can learn English from young age, in order to make them able to communicate using English in the spoken and written form. In the teaching learning of English, there are four basics skills that student must have. They are; listening, reading, speaking, and writing. Each skill can not be separated because they are main skills to master English as our foreign language. All of those four skills are important elements which can develop the students’ ability to communicate using English both in spoken and written. (Depdiknas, 2006) is also stated that the purpose of taught English subject at school is making the students able to build their communicative competence in spoken and written form. From those statement we can conclude that the goverment expects the students to be able to use English fluently, accurately, and acceptably both in spoken and written form. In addition, we can also conclude that writing is one of important communicative competence that have to be learned by all of the students. Writing is one of important skill in learning English as foreign language. We can share everything that we want freely in written form, it is supported by (Hyland, 2002) that writing can make the students take out their ideas in their mind and put it into others form that other people can read and consider it. It means that every person can share their idea and can communicate with others in the written form. However, communicating through writing is considered more difficult to use than spoken form. As stated by (Hadfield & Hadfield, 1990), for teacher of foreign language, writing lesson has a difficulty, and this also true for their students. For example in speaking, a speaker can explain and repeat more in order to make the receiver know what they mean. Moreover, it is supported by their gestures, intonations, or facial expressions. While in writing, the writer must be able to make their writing understandable without explaining and repeating it directly to the readers. In the same case, many students get some difficulties in mastering writing skill. It comes when they want to start their writing. The obstacles can appear from theirselves and from the environment. The first difficulty appears when the students don’t know what should they write in their written assignment because they have written about the topic many times. For instance, in the 8th and 9th grade of Junior High School the students have been taught narrative text, moreover they have to be able to write that text theirselves. When they asked by the teacher to write a narrative text, they were attending to write the topic as same as before because they were reluctant to write it with the new topic. It makes the students do not have anything left to write about in their narrative text writing assignment. Not only that, the other difficulty is also come when the students know what they are going to write, but they can’t organize it well. That happens because the students have lack in remembering the important writing elements, such as; vocabulary, transition signals, words connectors, and etc. which are very useful to help them in organizing written assignment. Facing that problems above, the sudent should be able to develop their writing skill by practicing it in particular time. (Patel & Jain, 2008) said that writing is skill that should be taught through practice. In the other hands, writing should be learned regularly in order to make the students’ skills in writing increase. There are several phases that should be followed by students to start their writing; first, the students should know and understand about grammatical features that is used in each sentence; second the students should be able to write their written assignment through English effectively; and the student should be able to use correctly conversations in peculiary language. Furthermore, the teacher can help the students to develop all of those phases above by using text type to teach writing skill. There are lots of text type that are taught in Senior High School, namely; recount, review, descriptive, narrative, analytical exposition, hortatory exposition, news item, explanation, narrative, procedure, anecdote, report, and discussion (Depdiknas, 2006). All of those text has different function, generic structure, and language features. From all types of the texts above, narrative is the text which is dominantly and frequently thought to the junior high schools and senior high schools students. Narrative text is a composition which tells about story. It can be factual and non-factual narrative text. Factual narrative text is kind of narrative which is related to the real story, for instance; someone experience, adventure, and historical event. While, non-factual narrative text is kind of story which is not real happen in our lives. For instance; myth, fairytale, legend, and fable. The purpose of this text is entertaining the readers. Moreover, we can use this kind of text when we want to tell about something interesting that happened or when we want to write some events of the day in the privacy in our diary. According to (Parera, 1993) the most narrative text have characteristic to tell a story of an event or events in chronological order in which they occured in time. The generic structure of narrative text consists of Orientation, Complication, Resolution, and Coda (Depdiknas, 2006). Coda is optional, sometimes it exists at the end of the story but sometimes it does not. According to (Nunan, 1991) the generic structure of narrative text consists of Orientation, Complication, and Resolution. Orientation is considered as the beginning of the story. This beginning is usually introduces the main character(s), time, and places (Depdiknas, 2006). It means that orientation generally gives the answer of where the action is located, who is (are) involved, and when the story happened. After that the story is going on by series of events which involve the main character(s) to some sort of problems. It called complication. The events in complication make the story more attractive. Finally, in the end of the story the reader will find resolution of the problem. The resolution that provided in the stoy can be better or worse. Sometimes coda exists after the resolution. It is a change that happened to the character and the leson that can be taken from the story or sometimes we called it as moral value from the story. Moreover, (Derewianka, 1990) described that narrative has some components of language features, those are; choose the descriptive language to enhance and develop the story by creating images in the readers’ mind, and the last participant can be written in the first person (I, we) or third person (he, she, they). It also mentioned in detail that narrative’s languag features are consist of the use of specific participants; mainly uses action verbs; use temporal conjunction and temporal circumstances; use past tense as dominant tense; and use relational and mental process. To deal with, the objectives of this study are describing the tenth graders narrative text in terms of its generic structure and language features. METHODOLOGY Since the researcher wants to analyze and describe the students’ narrative text writing, a descriptive qualitative research was conducted in this study. According to (Ary, Jacobs, & Sorensen, 2010) descriptive research involves describing and interpreting the nature and incidence as it exists at the time of study. Furthermore, in other pages they also said that descriptive research studies are designed to obtain information concerning the current phenomena. Simply, we can say that descriptive qualitative research is a research that describe the natural phenomena. In line with that statement, the researcher wanted to describe and observe the real condition that she faced in the field. She joined the teaching learning process on the day when the teacher gave writing assignment for the students. Because it helped the researcher to know the originality of students’ narrative text composition. The subject of this study were the tenth graders of acceleration class at SMA Negeri 1 Sidoarjo. This class was choosen because all of the students who entered in this class had high qualification than others. The researcher devided all of the students in this class into three different group based on their ability in mastering English; first contains students who have high ability in mastering English, second contains three students who have average ability in mastering English, and third contains students who have low ability in mastering English. But then, the researcher just took nine students’ narrative text as representatives to be analized. All of these representatives were taken from each group. The data in this study were generic structure and language features that used by the students in their narrative text. Therefore, the original students’ narrative text were collected by the researcher as source of data. The students’ narrative text was written in the same topic. The topic is about Bawang Merah and Bawang Putih. This study used three kinds of research intruments. First, the researcher herself. The researcher was the key of instrument in descriptive qualitative research because she had to analyze and describe all of the students’ narrative text. The second instrument was checklist. This checklist used to know how the teaching learning process went in the day that teacher gave the assignment for the students. The checklist included three main indicators, namely; teachers’ action, students’ response, and the materials given. The last instrument was assessment scoring rubric for generic structure and language features. Both of these rubrics was very useful for the researcher as a guideline to analyze the students’ narrative text. Furthermore, the researcher analized all of data she got based on Creswell theory at (Ary, et al., 2010). There were three steps to analyze the data in descriptive qualitative research, such as; (1) Organizing the data or data managing; (2) coding or classifiying; and (3) intrepetating or representing the data. FINDINGS AND DISCUSSIONS Based on the findings, all of the students in that three groups were able to write their narrative text completely in the term of generic structure. And they could write the orientation, then complication, and ended by resolution. But, the researcher found some errors that students did in their writing. The errors came from each part of generic structure which wrote by the students. Some of them made their errors in the orientation part, complication part, and resolution part. In this case, the first group students were included in the excellent category by the researcher because she did not find some errors in the students’ writing. They composed their narrative text completely without forgetting one component of its generic structure. They also wrote it correctly as its criteria in the generic structure rubric. First, the orientation part contains time and place where the story happened, characters inside, and the situation there. Second, the complication part explain about the series of events and climax of the story which shoud be written chronologically. Then, the resolution should be solved all of the problems that faced by the main characters in sequence and comprehensible. For instance, it can be seen from student 2’s narrative text writing. Student 2 could compose a very good story and organized it well. In her narrative text, student 2 was success write the orientation part as well by stating the time and the place related to the story, mentioned the characters inside the story, and gave a clear situation to draw how the story begins. Then, it continued by giving series of events which was written chronologically until met its climax. Then, after student 2 wrote out all of the problems and the climax of the story, she ended the story by writing the solution to solve the problems in the resolution part. In short, student 2 was able to applied narrative’s generic structure very well without missing one criteria of it. Close to the first group students, the three students in the second group were also able to implement narrative’s generic structure. They wrote the story start from the orientation, complication, and resolution. But, they could not composed each of the generic structure well. They missed some of criteria that should be in that part. For instance, two of the students in this group were not able to write the complication part correctly. Sometimes, they wrote it unchronologically, missed many events, and did not write the complication. Furthermore, there was a student in this group who wrote the climax of the story in the resolution part. It can be seen in the student 1’ resolution. He wrote the climax there to begin the resolution and gave the solution of the climax in this part too. It made the resolution part of his story was not suitable with the criteria in generic structure’s rubric. Another students also did not compose their orientation part completely. They did not include one criteria which should be stated in this part. Therefore, all of the students in this group were included in the very good category in implementing narrative’s generic structure. Since in the third group were consist of low level students in mastering English, the result of their narrative writing was also different from the first and second group before. Altough all of the students in this group could compose their narrative text based on its generic structure, the researcher still found many serious errors there. For instance, student 2 wrote a very simple orientation. He just wrote the time when the story happened and the characters which appeared there. This student was also missed some events which related to the climax in the complication part. In addition, the resolution part of his story was not composed well. He didn’t write the resolution part in sequence and directly gave the ending of the story. It makes the researcher included all of the students in this group into good category. From the result, the researcher found that all of the students in the third group were able to implement all of narrative’s generic structure in their text. But, some of them made errors when applying it. The errors mostly appeared when the students tried to write their narrative text using past tense as dominant tense there. Furthermore, the findings stated that all of students in the first group were able in applying five points of narrative’s language features correctly. Those five points were specific nouns as pronoun, time connectives, the use of action verb in the past form, the use of thinking verbs, and the use of past tense. Furthermore, it showed that student 2 in this group was able to use past tense perfectly as dominant tense in her narrative text. She was also able in using time connectives, action verbs in past tense, thinking verbs, and the pronoun to state the specific participant in the story. Furthermore, there were no spelling error, punctuation, capitalization, and other errors which were appeared in this group. It makes the researcher included all of the students into excellent category in the terms of language features. Almost same with the first group, the three students in the second group were also able in applying narrative’s language features in their writing. But, they still made error when used past tense in their narrative text. Moreover, all of them also made some errors in spelling, punctuation, and especially in capitalization. Generally, their narrative text was good, the errors happened because they needed more concentration in apllying narrative’s language features. The researcher gives some excuses to the students since it just a simple error and did not have serious impact to the students’ writing. This fact was different from the students in the third group. Three students who were belonging in this group faced many problems. The problems were coming from the use of past tense, action verbs, and the thinking verbs in their narrative writing. For instance, one of student in this group made a serious error by using present tense and present action verbs in her narrative text. She often translated Indonesia directly into English without obeying the sentence structure. It showed that she was not able to write a simple correct or complex past and present tense. Moreover, the errors of spelling, punctuation, and capitalization were also appeared frequently in students’ narrative text in this group. Their sentence structures were different between what was in their mind and their writing. So, it makes the researcher little bit confused to get the point in their narrative text. Fortunately, all of the students in this group were able in using pronoun and time connectives in their narrative text properly. CONCLUSIONS AND SUGGESTIONS Conclusions From the findings, it was found that the tenth graders especially acceleration class of SMA Negeri 1 Sidoarjo have organized all of the narrative text components in their writing assignment. They were able to implement both of generic structure and language features of narrative text properly. At the generic structure stage, all of students in the three groups were able to write their narrative text based on its generic structure. They started their story from the orientation, continued with complication, and ended by resolution. But, all of those three groups were included in different category by the researcher. First, the students who belongsgs to the first group were able to apply all of narrative’s generic structure with correct criteria. So, it makes the researcher included all of them into excellent category. Second, the researcher included the second group into very good category. Because they made small error when applied narrative’s generic structure. The error happened when the students in this group did not include one of the criteria that should be stated in each part of generic structure. Then for the last group, the researcher included all of the students there into good category. Because all of the students there made serious error when applying each part of narrative’s generic structure. They did not include some of criteria which were should be stated in the generic structure’s part. At the same time, most of students in these three groups were able to apply all of the language features of narrative text. They could use past tense as the dominant tense there, action verbs in the past form, mental or thinking verbs, time connectives and mentioned the specific nouns as pronoun. But, some of them were not able to apply it well. They tended to make error when using past tense as the main tense in this text. Moreover, some students were still difficult to express their ideas using the right sentence structure specially in the use of simple past tense. It made their sentence difficult to understand by the readers. As a result, the reader would not get the point of the story. In line with that, there was one error that almost all of the students did. The errors were forgetting to use capital letter in the first word of every sentence and did not use the punctuation correctly. So, it still can be concluded that the tenth graders of SMA Negeri 1 Sidoarjo are able to write the narrative text in the terms of generic structure and language features. Suggestions At the end, some suggestions are offered that related to the result of this study. First, the teachers should give a clear explanation when teaching narrative text in classroom. Because it will make the students more understand about narrative text itself. They will know the each part of narrative generic structure and its criteria. In addition, since past tense is used as dominant tense in narrative text, it is better for the teacher to give brief and clear explanation about it before they give assignment to the students. Because, most of the students made some errors in the use of past tense in their writing. Moreover, the teacher should pay more attention or gave comments to the students’ writing which is very useful suggestion for them in the next writing activity. REFERENCES Agustin, H. I. R. (2004). The 2004 Curriculum in a Nutshell. Malang: Universitas Negeri Malang. Anker, S. (2010). The Real Writing with Reading (Vol. Fifth Edition, Ary, D., Jacobs, L. C., & Sorensen, C. (2010). Introduction to Research in Education. Canada: Nelson Education, Ltd. Bailey, S. (2011). Academic Writing A Handbook for International Students Brown, H. D. (2004). Language Assessment Principles and Classroom Practices. USA: Pearson Longman. Brown, J. W. (1983). AV nstruction: Technology, Media, and Methods. New York: McGraw-Hill, Inc. Brown, K., & Hood, S. (1993). Writing Matters Writing Skills and Strategies for Students of English Depdiknas. (2006). Kurikulum Tingkat Satuan Pendidikan SMA dan MA. Jakarta: Depdiknas. Derewianka, B. (1990). Exploring How Text Work. Australia: Primary English Teaching Association. Hadfield, C., & Hadfield, J. (1990). Writing Games. Hongkong: Thomas Nelson and Sons, Ltd. Hyland, K. (2002). Teaching and Researching Writing. London: Pearson Education. Irawati, D. (2011). Language Features and Generic Stuctures Analysis of Descriptive text Written by the Tenth Grade Students of SMUN 21 surabaya., State University of Surabaya, Surabaya. Kane, T. S. (2000). THE OXFORD Essential Guide to Writing Mercer, C. D., & Mercer, A. R. (1989). Teaching Students with Learning Problems. Colombus: Merill Publishing Co. Mitra, M. M. (2012). An Analysis of Students' Writing Assignment of Analictical Exposition Text Written By The Eleventh Graders. State University of Surabaya, Surabaya. Nunan, D. (1991). language Teaching Methodology: A Textbook for Teacher. London: Prentice Hall International (UK) Ltd. Oshima, A., & Hogue, A. (2006). Writing Academic English. New York: Pearson Education, Inc. Oxford Learner's Pocket Dictionary. (2008) (Vols. Fourth Edition). New York: Oxford University Press. Parera, J. D. (1993). Menulis Tertib dan Sistematis (Vol. Kedua). Jakarta: Erlangga. Patel, D. M. E., & Jain, P. M. (2008). English Language Teaching (Methods, Tools, & Techniques) Jaipur: Sunrise Publishers and Distributors. Reid, J. M. (1993). Teaching ESL Writing. New Jearsey: Prentice Hall, Inc. Setyorini. (2009). The Student's Writing Ability to organize Narrative Genre. State University of Surabaya. www.centralischool.ca/ bestpractice/rubrics/writing.html access on March, 23rd 2013 at 18.00 WIB